THE EFFECT OF CRUDE OILS ON THE METALLIC CORROSION AND THE STABILITY OF METALS IN A CORROSIVE ENVIRONMENT - Aluvihara, Suresh; Premachandra, Jagath K (MATTER: International Journal of Science and Technology, 2019)
Crude oil is a supreme earth resource that essential in most of industrial applications while having some adverse effects in the crude oil refining process regarding metals such as the corrosion. According to the general definition usually the corrosion is the formation of metal oxides, sulfides, hydroxides or any compound related with carboxylic group. In the environment of crude oils the corrosion is highly depended on the sulfur, organic acids, mercaptans and salts composed in crude oils and also the chemical compositions of such metals. In the current research it was expected to investigate the relative effects of corrosive properties on the rate of corrosion in seven selected types of metals which are frequently used in the Sri Lankan crude oil refining industry and the stability of those metals against the effect of both Murban and Das Blend crude oils regarding the composition and properties. Corrosive properties of both crude oils were determined using in order to XRF analyzer, titration methods and salt analyzer also the chemical compositions of each metal was determined by XRF detector. Batches of equal sized metal coupons from seven types of metal were dipped in crude oils separately and their corrosion rates were determined after 15, 30 and 45 days while observing through an optical microscope. The metallic concentration in each crude oil sample was tested by AAS. The initial and the hardness after the corrosion were tested in each metal coupon. According to the observed results Das Blend was ahead regarding sulfur content, mercaptans content and acidity even though higher corrosion rates were shown by four types of metals in Murban than the corrosion rate in Das Blend. The slight reductions in the hardness were found in each metal coupon and some significant metallic concentrations were found in both crude oils regarding some metals forever.